Changing epidemiology and trends in incidence of oesophageal cancer in England, 1985-2017. (20th October 2021) - Chimba, C; Bannister, P; Memon, A
Abstract: Background: The incidence of oesophageal cancer has been steadily increasing over the past 30 years in many countries. The UK has the highest incidence of oesophageal adenocarcinoma in the world which is associated with obesity and gastro-oesophageal reflux disease. The study aimed to determine trends in the incidence of oesophageal cancer in England between 1985-2017. Methods: Individual-level data for patients diagnosed with oesophageal cancer in England were obtained from the Office for National Statistics/Public Health England. The national population-based cancer registry data were analysed to determine changes in oesophageal cancer incidence (ICD-10 code: C15) by sex, age (0-49, 50+) and histological subtype. Percentage change in incidence rates was calculated using the change in average annual incidence rate from the first (1985-89) to the last time period (2015-17). Results: During the 33-year study period, 199, 489 cases of oesophageal cancer were registered in England (63.5% males, 36.5% females) with adenocarcinoma accounting for 50.9% of cases. The average annual number of cases increased from 4595/year in 1985-89 to 7612/year in 2015-17. The average annual incidence rates increased by 42%, from 9.7/100, 000 in 1985-89 to 13.8/100, 000 in 2015-17. The incidence of adenocarcinoma increased by 77%, from 4.6/100, 000 in 1985-89 to 8.1/100, 000 in 2015-17. The incidence of squamous-cell carcinoma was unchanged. The steepest increase in adenocarcinoma was observed in males (more than two-folds as compared to females). Conclusions: Over the study period, there was an increase in the incidence of oesophageal cancer in England. The largest increase was seen in rates of adenocarcinoma. Considering obesity has a strong temporal association with oesophageal adenocarcinoma, further research is needed to understand the biological mechanisms of this association to inform public health efforts to reduce the prevalence of obesity. Key messages: Further research and analysis of routinely collected data on histological subtypes of oesophageal cancer can provide insight into the increasing trend in incidence. Considering the strong association between obesity and oesophageal adenocarcinoma, this research highlights the benefits of reducing the prevalence of obesity.